REVIVE-ing a Weak Heart — Details Matter - Kirtane, Ajay J. (The New England journal of medicine, 2022)
Ischemic cardiomyopathy represents the pathophysiological convergence of two growing clinical problems: atherosclerotic coronary artery disease and congestive heart failure. When a patient presents with congestive heart failure, it is incumbent on clinicians to undertake an etiologic workup that includes evaluation for a diagnosis of coronary artery disease 1 ; simply establishing a diagnosis of coronary artery disease has been associated with greater use of guideline-directed medical therapies among patients with congestive heart failure. 2 When it is severe, coronary artery disease is often assumed to be the cause of left ventricular dysfunction. Apart from the accuracy of that assumption, a further open question . . .